Paul's metaphors their context and character - Williams, David John (Peabody, MA Hendrickson, 1999)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. Epistles of Paul -- socio-rhetorical criticism; Metaphor in the Bible